Determinants of Employment Opportunities in Kotawaringin Barat Regency: An OLS Approach - Hasaruddin Hasaruddin; Siti Khotimah (MANABIS: Jurnal Manajemen dan Bisnis, 2026)
Employment opportunities are an important indicator of regional economic development because they reflect the ability of an economy to absorb labor and improve community welfare. This study aims to analyze the effects of economic growth, labor force, inflation, and investment on employment opportunities in Kotawaringin Barat Regency during the period 2011–2025. The study employs a quantitative approach using secondary time-series data obtained from Statistics Indonesia (BPS), the Regional Development Planning Agency (Bappeda), and other relevant institutions. Multiple linear regression analysis based on the Ordinary Least Squares (OLS) method was applied using EViews software. Prior to hypothesis testing, classical assumption tests consisting of normality, multicollinearity, heteroscedasticity, and autocorrelation tests were conducted to ensure the validity of the model. The results indicate that economic growth, labor force, and investment have positive and statistically significant effects on employment opportunities. Economic growth exhibits the strongest influence, indicating that regional economic expansion substantially contributes to labor absorption. Meanwhile, inflation has a negative and significant effect on employment opportunities, suggesting that rising prices may reduce firms’ capacity to create jobs. Simultaneously, economic growth, labor force, inflation, and investment significantly affect employment opportunities, with an R² value of 0.9274, indicating that 92.74% of the variation in employment opportunities is explained by the variables included in the model. The findings imply that policies aimed at sustaining economic growth, improving labor quality, maintaining price stability, and encouraging investment are essential for expanding employment opportunities and reducing unemployment in Kotawaringin Barat Regency.